2011
DOI: 10.17221/392/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

A new look at the assessment of the silver carp (Hypophthalmichthys molitrix Val.) as a food fish ;

Abstract: Buchtová H., Ježek F. (2011): A new look at the assessment of the silver carp (Hypophthalmichthys molitrix Val.) as a food fish. Czech J. Food Sci., 29: 487-497.The principal aim was to analyse the chemical composition (dry matter, protein, fat, saccharides, ash) and to calculate the energy value of 6 topographically distinct parts (cranial, medial and caudal dorsal/ventral part above/below the lateral line) of the fillets of the silver carp (Hypophthalmichthys molitrix Val.) in two weight categories, i.e. lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…It was indicated that, Chanodichthys erythropterus contain a higher proportion of protein and lower ash content as indicated from the results obtained. Previous studies on proximate analysis by Buchtová et al [23] on a different fish species from the same family confirms the results obtained in this research, however, reports from Ashraf et al [24] are not in concordance with it as they reported higher moisture content and relatively lower protein content for silver carp. This difference might be due to genetical factors as well as extrinsic factors such as feeding regimes and/or exercise significant change in some structural and flesh quality parameters of different fish species.…”
Section: Proximate Compositionsupporting
confidence: 77%
“…It was indicated that, Chanodichthys erythropterus contain a higher proportion of protein and lower ash content as indicated from the results obtained. Previous studies on proximate analysis by Buchtová et al [23] on a different fish species from the same family confirms the results obtained in this research, however, reports from Ashraf et al [24] are not in concordance with it as they reported higher moisture content and relatively lower protein content for silver carp. This difference might be due to genetical factors as well as extrinsic factors such as feeding regimes and/or exercise significant change in some structural and flesh quality parameters of different fish species.…”
Section: Proximate Compositionsupporting
confidence: 77%
“…The middle cut has comparatively more percentage of edible fillet yield; the fore cut has the higher relative bone content. It is well known that in Hypophthalmichthys molitrix the hind cut is comparatively larger and has more meat and bone when compared with other species (Romavari et al., ; Buchtova and Jezek, ).…”
Section: Discussionmentioning
confidence: 99%
“…Buchtova and Jezek () demonstrated a significant difference in fat composition between the leaner dorsal part of the silver carp fillet, which ranks among medium to low‐fat fish of 4.6 and 5.1% with live weights of 3.5 and 4.5 kg, respectively; the fatter ventral part ranks the silver carp among the high‐fat fish of 15.8 and 15.7% with weights of 3.5 and 4.5 kg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This fish is a specialized plankton feeder that by preference feeds off phytoplankton (Kolar et al . ) and is known to assimilate n‐3 fatty acids (Buchtová & Jezek ). It is possible that crocodiles and catfish feed on silver carp when these seasonally migrate from the still waters of the lake into the Olifants River to spawn, and this may provide one explanation for intense intake of excessive polyunsaturated fats by catfish and crocodiles.…”
Section: Resultsmentioning
confidence: 99%